Végétation des espaces boisés et paysage urbain - Francesca Di Pietro; Lotfi Mehdi (Projets de Paysage)
This article presents research conducted on the vegetation associated with trees in urban wooded areas, and its relationship to the landscape in a medium-sized city: the agglomeration of Tours. An in-depth study of the vegetation of urban wooded areas made it possible to study the links between this flora and 1) the urban spatial structure (central and peripheral wooded areas) and 2) the internal spatial structure of wooded clusters (central and outlying zones). The urban structure plays a dominant role in the botanic compositions of the woodland undergrowth: the central wooded areas (surrounded by a high proportion of urbanised surfaces) harbour almost all the horticultural species present, thus contributing to their diversity. The peripheral woods, extensive and mainly surrounded by cultivated land, do not present a higher degree of diversity compared to the central wooded areas. The proportion of woodland surface area compared with the urbanised surface areas adjacent to wooded areas of varying radiuses, are major factors in the botanic compositions of urban woods. In the interrelation between the internal spatial structure of urban wooded areas and the vegetation of the woods, the outskirts of the woods have a specific diversity which is greater than that of the central zones, even though the plant communities of the central and outlying zones are very similar. Our results confirm elements identified in large agglomerations: spontaneous vegetation in urban wooded spaces is linked to the structure of the urban landscape; urban forestry management strategies should take into account the colonisation process of semi-natural vegetation at the level of the landscape.